Pelanggaran Prinsip Kerja sama dalam Debat Pemilihan Umum Calon Presiden 2019 - Sofiana, Sofiana; Hermaliza, Hermaliza (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
Violation is an act or case of violating applicable rules or regulations. Speakers and speech partners in communicating must comply with the principle of cooperation, but in the 2019 Presidential Candidate General Election debate the author found speeches that violated the principle of cooperation. This is what makes the author interested in conducting this research entitled "Violation of the Principle of Cooperation in the 2019 Presidential Candidate General Election Debate". This study aims to determine the violation of the Principles of Cooperation in the 2019 Presidential Candidate Election Debate. The problem in this research is how the violation of the principle of cooperation in the 2019 presidential election debate. The theory used by the author is the theory of Grice in Wijana (1996), and Grice in Rahardi (2005). This research falls within the scope of pragmatics, in particular the principle of cooperation. Sources of data in this study are the entirety of the speeches between the debate moderators and the pairs of presidential and vice presidential candidates for the 2019 presidential election debate, while the data in this study are all violating speeches in the five debate sessions on the 2019 presidential candidate general election. The method I use is the method content analysis, the type of research is library research, and the research approach is a qualitative approach. Data collection techniques are carried out through documentation techniques, hermeneutic techniques. The conclusion in this study is that the results of violation of the maxim of cooperation principle from the first debate to the fifth debate, the speech violating the maximal quantity of 14 speeches, maxim of quality of 25 speeches, maxim of relevance of 26 utterances, maxim of implementation or way of 19 utterances, the tendency of speech participants in the debate with partners said many violate the principle of cooperation.